Analysis Of Work Stress, Work Conflict And Organizational Commitment To Employee Performance At The Office Of The Baerah Revenue Agency (Bapenda) Of North Sumatra Province - Lubis, Ira Handayani; Juniarti, Juniarti; Waruwu , Ahmad Aswan (Journal of Management, Economic, and Accounting, 2025)
This study was conducted to determine the effect of work stress, work conflict, and organizational commitment on employee performance at the Regional Revenue Agency (Bapenda) of North Sumatra Province. The research approach used was quantitative with a descriptive quantitative research design involving numerical data and statistical analysis using SPSS Version 26. The study population consisted of all civil servants working at the Regional Revenue Agency (Bapenda) of North Sumatra Province, totaling 181 employees. The sampling technique employed was probability sampling using random sampling with the Slovin formula, with a margin of error of 10%, resulting in a sample size of 64 employees. The results of this study indicate that work stress has a positive and significant partial effect on employee performance with a tvalue > ttable (31.613 > 2.00030) and work conflict has a positive and significant partial effect on employee performance with a tvalue > ttable (19.004 > 2.00030), and organizational commitment has a positive and significant partial effect on employee performance with a tvalue > ttable (12.048 > 2.00030). Simultaneously, work stress, work conflict, and organizational commitment have a positive and significant effect on employee performance at the Regional Revenue Agency (Bapenda) of North Sumatra Province, with the calculated Fvalue > Ftable (1224.415 > 2.76). The results of this study indicate that H1 is accepted and H0 is rejected, both partially and simultaneously. The coefficient of determination obtained is 98.3%, with the remaining 1.7% explained by other independent variables not examined in this study.